Minahasa Utara Menuju Bebas Stunting - Hendayana Hendayana (Universitas 17 Agustus 1945, 2023)
One of the development frameworks for North Minahasa to be more advanced is that the government continues to improve and improve programs on stunting prevention in North Minahasa Regency, because in the last 5 years the stunting prevalence rate in North Minahasa is quite high, even in 2018 North Minahasa Regency became a district. with the highest stunting rate in North Sulawesi reaching 35.44%. Therefore, the authors are interested in conducting research with the title